A Specific Groove Pattern Can Effectively Induce Osteoblast Differentiation. (9th October 2017) - Kim, Chang‐Su; Kim, Jin‐Hee; Kim, Bokyoung; Park, Young‐Seok; Kim, Hong‐Kyun; Tran, Hieu Trung; Kim, Sang Hoon; Jeon, Hojeong; Kim, Sangjib; Sim, Ji Hyun; Shin, Hyun Mu; Kim, Gwanghun; et al.
Abstract: Little is known about the principles of surface structure design for orthopedic and dental implants. To find topographical groove patterns that could enhance osteoblast differentiation according to cell type, groove patterns are fabricated with ridges (0.35−7 µm) and grooves (0.65−6 µm) of various widths and explored their mechanisms in improving osteoblast differentiation. This study finds that a groove pattern enhancing osteoblast differentiation is associated with the ability of the cell to extend its length and that it is able to overcome the inhibition of osteoblast differentiation that takes place under inflammatory conditions. The groove pattern suppresses the generation of reactive oxygen species, a reaction that is increased in inflammatory conditions. It also modulates the expression of osteogenic factors according to differentiation time. Importantly, specific groove patterns AZ‐2 and AZ‐4, with ridge width of 2 µm and groove width of 2 or 4 µm, respectively, effectively promote bone regeneration in critical‐sized calvarial defects without additional factors. This knowledge of groove patterns can be applied to the development of orthopedic and dental devices. Abstract : A groove pattern enhancing osteoblast differentiation is associated with the ability of the cell to extend its length and that it is able to overcome the inhibition of osteoblast differentiation and effectively promotes bone regeneration in calvarial defects. This knowledge of groove patterns can be applied to the development of orthopedic and dental devices.